Rifampicin-loaded ‘flower-like’ polymeric micelles for enhanced oral bioavailability in an extemporaneous liquid fixed-dose combination with isoniazid - Moretton, Marcela Analía (2014)
BACKGROUND: Coadministration of rifampicin (RIF)/isoniazid (INH) is clinically recommended to improve the treatment of tuberculosis. Under gastric conditions, RIF undergoes fast hydrolysis (a pathway hastened by INH) and oral bioavailability loss. AIM: We aimed to assess the chemical stabilization and the oral pharmacokinetics of RIF nanoencapsulated within poly(ε-caprolactone)-b-PEG-b-poly(ε-caprolactone) 'flower-like' polymeric micelles. MATERIALS & METHODS: The chemical stability of RIF was evaluated in vitro under acid conditions with and without INH, and the oral pharmacokinetics of RIF-loaded micelles in rats was compared with those of a suspension coded by the US Pharmacopeia. RESULTS: Nanoencapsulation decreased the degradation rate of RIF with respect to the free drug. Moreover, in vivo data showed a statistically significant increase of RIF oral bioavailability (up to 3.3-times) with respect to the free drug in the presence of INH. CONCLUSION: Overall results highlight the potential of this nanotechnology platform to develop an extemporaneous liquid RIF/INH fixed-dose combination suitable for pediatric administration.